Pengalaman Ibu Melahirkan di Rumah Pada Masa Covid-19 - winda pratiwi; Yulia Irvani Dewi; Erika (STIKes Payung Negeri Pekanbaru, 2022)
Cases COVID-19 is increasing every day which has an impact on all sectors including maternal services. Mothers giving birth are a vulnerable group, during the delivery process the mother is required to follow health protocols, this raises concerns and decides to undergo the delivery process at home. This study aims to explore the experiences of mothers giving birth at home during the COVID-19 period. The research design used descriptive phenomenology with semi-structured interviews. The study was conducted in the working area of ​​the Paraman Ampalu Public Health Center, West Pasaman Regency, West Sumatra, with 5 participants selected by purposive sampling technique. Data analysis using thematic analysis stages according to Collaizi. The experience of mothers giving birth at home during the COVID-19 period found 4 themes, namely: 1) Differences in the experience of mothers undergoing the birth process before and during the COVID-19 period, 2) The advantages and disadvantages of undergoing the birth process at home during the COVID-19 period, 3) Support received by mothers during the birth process at home during the COVID-19 period, 4) Expectations and suggestions of mothers who underwent the birth process at home during the COVID-19 period. The results of this study describe the phenomenon that participants choose to give birth at home with various considerations for reasons of safety and comfort, especially during the COVID-19 period. It is hoped that health workers will pay more attention to delivery assistance by health workers and modify maternal health services in COVID-19 period.